Studying Early Printed Books, 1450-1800 A Practical Guide - Werner, Sarah 1969- (John Wiley & Sons, Incorporated, 2018)
Intro -- Title Page -- Copyright Page -- Contents -- List of Illustrations -- Acknowledgments -- Introduction -- Part 1 Overview -- Getting Ready to Print -- At the Press -- Also at the Press -- After Printing -- The Economics of Printing -- Part 2 Step‐by‐Step -- Paper -- Type -- Format -- Printing -- Corrections and Changes -- Illustrations -- Binding -- Part 3 On the Page -- Advertisements -- Alphabet and Abbreviations -- Blanks -- Dates -- Imprint Statements -- Edition, Impression, Issue, State, Copy -- Initial Letters -- Marginal Notes -- Music -- Pagination and Foliation -- Preliminary Leaves -- Press Figures -- Printer's Devices -- Printer's Ornaments -- Privileges, Approbations, and Imprimaturs -- Signature Marks -- Title Pages -- Volvelles and Movable Figures -- Part 4 Looking at Books -- Good Research Habits -- Handling Books -- Appearance -- Contents -- Page Features -- Usage -- Digitization -- Part 5 The Afterlives of Books -- Loss Rates -- Catalog Records -- Books in Hand -- Books on Screen -- Conclusion -- Appendix 1 Further Reading -- General Bibliography -- Printer's Manuals -- History of the Book -- Book Trade -- Manuscripts and Paleography -- Handling Books -- Catalogs of Early Hand‐press Books -- Catalog and Imprint Resources -- Paper -- Type -- Format -- Printing -- Corrections -- Illustrations -- Bindings -- On the Page -- Afterlives -- Digital Collections -- Appendix 2 Glossary -- Index -- EULA